Realistic Evaluation of the Integrated Electronic Diagnosis Approach (IeDA) for the Management of Childhood Illnesses at Primary Health Facilities in Burkina Faso - Karl Blanchet; Vincent-Paul Sanon; Sophie Sarrassat; Arsène Satouro Somé (Kerman University of Medical Sciences, 2023)
Background  In 2014, Terre des Hommes (Tdh) together with the Ministry of Health (MoH) launched the Integrated electronic Diagnosis Approach (IeDA) intervention in two regions of Burkina Faso consisting of supplying every health centre with a digital algorithm. A realistic evaluation was conducted to understand the implementation process, the mechanisms by which the IeDA intervention lead to change.Methods  Data collection took place between January 2016 and October 2017. Direct observation in health centres were conducted. In-depth interviews were conducted with 154 individuals including 92 healthcare workers (HCW) from health centres, 16 officers from district health authorities, 6 members of health centre management committees. In addition, 5 focus groups were organised with carers. The initial coding was based on a preliminary list of codes inspired by the middle-range theory (MRT).Results  Our results showed that the adoption of the electronic protocol depended on a multiplicity of management practices including role distribution, team work, problem solving approach, task monitoring, training, supervision, support and recognition. Such changes lead to reorganising the health team and redistributing roles before and during consultation, and positive atmosphere that included recognition of each team member, organisational commitment and sense of belonging. Conditions for such management changes to be effective included open dialog at all levels of the system, a minimum of resources to cover the support services and supervision and regular discussions focusing on solving problems faced by health centre teams.Conclusion  This project reinforces the point that in a successful diffusion of IeDA, it is necessary to combine the introduction of technology with support and management mechanisms. It also important to highlight that managers' attitude plays a great place in the success of the intervention: open dialog and respect are crucial dimensions. This is aligned with the findings from other studies.